Development of Learning Devices Using the Missouri Mathematics Project (MMP) Model on Statistical Materials in Junior High Schools - Tessa Lestari; Abdurrahman (UIR PRESS, 2022)
This development research aims to produce learning device products using a valid Missouri Mathematics Project (MMP) model. The learning device products developed to consist of the Learning Implementation Plan (RPP) and Student Worksheets (LKPD). This type of research is development research with the ADDIE model, which has been modified into four stages (Analysis, Design, Development, and Evaluation). The data collection instruments used in this study were validation sheets and teacher response sheets to measure the validity and practicality of learning devices. The data analysis used is descriptive data analysis which describes the level of validity and practicality of the product. The data was obtained from the validation results by two mathematics education lecturers and two mathematics education teachers. The results obtained in the form of RPP validation results are 83.33% with valid criteria, and LKPD validation results are 87.88% with very valid criteria, then the results of the practicality questionnaire for practical RPP with an average of 83.33% and LKPD in the category very practical with an average of 87.5%. Thus, it can be concluded that this development research resulted in learning tools (RPP and LKPD) that were tested for their validity and practicality.